USE OF NUCLEAR WEAPONS IN HUMANITER LAW ENFORCEMENT PERSPECTIVE - Arimbi Fajari Furqon (Indonesian Journal of Multidisciplinary Science, 2022)
Human life and technological developments are closely related to the legal awareness of the international community. The discovery of nuclear weapons for the first time was by the United States (US). It was used in World War II to attack and bomb the cities of Hiroshima and Nagasaki in 1945. The incident resulted in the death of 160,000 (one hundred and sixty thousand) people, and damage to almost all the ecosystem. The devastating negative effects resulting from the use of nuclear weapons were then regulated and contradicted the norms outlined in Additional Protocol I of 1977, to the 1949 Geneva Conventions which regulates the methods and methods of war. Although it has been regulated in the 1949 Geneva Conventions (international humanitarian law), however, it turns out that there are still many countries that continue to develop nuclear weapons for reasons of national security. The research method used is a type of normative juridical research and uses a statutory approach and conceptual thinking. The results of the study indicate that the governing norms regarding; research and possession of nuclear weapons are still discriminatory. In practice, there is a distinction between a nuclear state and a non-nuclear state. Furthermore, in the current reality, there are still countries that are classified as not having good intentions to carry out the agenda of disarming and stopping the development of nuclear weapons. Meanwhile, according to the results of this study, to overcome these problems, it is necessary to have new legal principles that can be universally binding.